A educação como ética contra o conformismo – repensando o papel do educador (Education as ethics versus conformism - rethinking the role of the educator) - Manzi Filho, Ronaldo (Revista Eletrônica de Educação, 2018)
Abstract This text intends to think education as ethics against conformism. Conformism is understood here as a certain form of naturalization. The text seeks to develop what it is understood by naturalization and it will confront this conception with the question of ideology as presented mainly in the lines of Marilena Chaui. The whole issue will turn to the ways in which education relates to the social. Some metaphors will be used to think this naturalization – just like the fetters that bind men in Plato’s description of cave myth; or Descartes mistrust of tradition in his re?ection on the discourse on the method. The frst metaphor will be circular: it will appear in every argument – since these fetters will be associated with our way of conforming to the social. The second metaphor will be used as an engagement in the ability to doubt. To get rid of shackles and to question tradition without ignoring it – this is a central question in this text. In relation to ethics, an intention of engagement and authenticity is not concealed here. The text will turn to some pedagogical proposals and will go to a line of thought that goes against the cultural industry: against the principles of information/entertainment that often appear in the pedagogical discourse today. Keywords: Naturalization; Ideology; Conformity; Transformation and ethics. Resumo Este texto pretende pensar a educação como uma ética contra o conformismo. O conformismo é entendido aqui enquanto uma certa forma de naturalização. O texto busca desenvolver o que se entende por naturalização e confrontará esta concepção com a questão da ideologia tal como se apresenta, principalmente, nas linhas de Marilena Chaui. Toda a questão irá se voltar às formas de como a educação se relaciona ao social. Usar-se-á algumas metáforas para se pensar esta naturalização – tal como os grilhões que acorrentam os homens na descrição de Platão no mito da caverna; ou a desconfiança de Descartes da tradição em sua re?exão sobre o discurso do método. A primeira metáfora será circular: irá aparecer em toda argumentação – já que estes grilhões serão associados à nossa forma de se conformar ao social. A segunda metáfora será usada enquanto engajamento na capacidade de se duvidar. Desvencilhar-se de grilhões e se questionar sobre a tradição sem a ignorar – eis uma questão central neste texto. Em relação à ética, não se esconde aqui uma pretensão de engajamento e de autenticidade. O texto se voltará a algumas propostas pedagógicas e irá se encaminhar a uma linha de pensamento que vai de encontro à indústria cultural: contra os princípios da informação/entretenimento que tanto aparecem no discurso pedagógico atualmente. Palavras-chave: Naturalização; Ideologia, Conformismo; Transformação e ética. References ADORNO, Theodor. The culture industry. Ed. J. M. Bernstein. London; New York: Routledge, 1991. AGAMBEN, Giorgio. Moyens sans fins – Notes sur la politique. Trad. Éditions Payot & Rivages. Paris: Éditions Payot & Rivages, 2002. ALTHUSSER, Louis. Ideologia e aparelhos ideológicos do Estado. Trad. Joaquim José de Moura Ramos. Lisboa: Presença, 1980. ARENDT, Hannah. A crise da educação. In: ______. Entre o passado e o futuro. Trad. Mauro W. Barbosa de Almeida. São Paulo: Perspectiva, 1972. BOÉTIE, Étienne de la. Discurso da servidão voluntária. Trad. Casemiro Linarth (edição bilíngue). São Paulo: Martin Claret, 2009. BOSI, ECLÉA. Cultura e desenraizamento. In: BOSI, Alfredo. Cultura brasileira – Temas e situações. São Paulo: Ática, 1987, pp. 16-41. CANGUILHEM, Georges. Le normal et le pathologique. Paris: PUF, 2007. CHAUI, Marilena. O que é ideologia. São Paulo: Abril Cultural, 1984. DESCARTES. Discurso do método. In: ______. Descartes (Os pensadores). Trad. Enrico Corvisieri. São Paulo: Nova Cultural, 1999, pp. 33-100. FREIRE, Paulo. Pedagogia do oprimido. Rio de Janeiro: Paz e Terra, 1987. FREUD, Sigmund. O mal-estar na civilização. In: ______. Obras completas – volume 18. Trad. Paulo César de Souza. São Paulo: Companhia das Letras, 2010, pp. 13-122. HEGEL, Georg W. F. Fenomenologia do Espírito – parte I. Trad. Paulo Meneses. Petrópolis: Vozes, 2000. HEIDEGGER, Martin. Ser e Tempo. Trad. Fausto Castilho (edição bilíngue). Campinas: Editora da Unicamp, 2012. KEHL, Maria Rita. Ressentimento. São Paulo: Casa do Psicólogo, 2004. MERLEAU-PONTY, Maurice. Phénoménologie de la perception. Paris: Gallimard, 1967. MERLEAU-PONTY, Maurice. Résumés de cours – Collège de France (1952-1960). Paris: Gallimard, 1968. PLATÃO. Republic. Trad. G. M. A. Grube. In: ______. Plato – Complete Works. Indianapolis/Cambridge: Hackett Publishing Company, 1997, pp. 1132-1155.